2022-RA-1159-ESGO Stump. (20th October 2022) - Saoud, Mohammed Karam; Taghzouti, Hanae
Abstract : Introduction/Background: Smooth muscle tumors of the uterus are subdivided into three categories: leiomyomas, leiomyosarcomas and STUMP (smooth muscle tumor of uncertain malignant potential). This classification is based on the study of 3 histopronostic criteria which are: nuclear atypia, mitosis index and the presence or absence of tumor necrosis. The STUMPs are smooth muscle tumors whose morphological characteristics do not allow them to be formally classified as benign or malignant tumors. The diagnosis of uterine sarcoma or stromal tumor of uncertain malignant potential must be evoked on MRI. Methodology: Six cases of STUMP treated in the department of gynecology-obstetrics I at the CHU Hassan II in Fez between 2017 and 2021 were analyzed retrospectively. Results: Of the 06 patients, 50% are multiparous. 80% of our patients consulted for metrorrhagia. All patients had surgical treatment. Anatomopathological analysis of the surgical specimens revealed STUMP in all cases. Conclusion: Uterine STUMP is a rare condition, and diagnosis can be difficult, often with unusual combinations of findings. Prognosis for the patient is unclear and their is a risk of recurrence with the tumors. To reduce mortality, regular follow-up and a centralised approach are recommended.